Setting up a gene expression study for tissue cells by method of quantitative real-time PCR - Daliborka DUŠANIĆ; Luka BOLHA; Mojca NARAT; Irena OVEN (Acta Agriculturae Slovenica, 2012)
Gene expression analysis by quantitative reverse transcription polymerase chain reaction (RT-qPCR) allows accurate and sensitive measurment of gene expression levels. However, a series of steps needs to be taken to ensure the relevance, accuracy, correct interpretation and repeatability of the RT-qPCR experiment. We describe here a simple experiment of determining relative gene expression for caspase 8 gene in chicken chondrocytes treated with an apoptosis inducing compound 5-fluorouracil. We use this example to point out some important guidelines in setting up a gene expression study in tissue cells, analyzing and interpreting the results and reporting on the findings.